EP1213 Comparison of survival between abdominal versus laparoscopic radical hysterectomy in cervical cancer: 10 year experience in a single UK cancer centre. (1st November 2019) - Gomes, N; Dasgupta, A; Blake, D; Fisher, A; Ratnavelu, N; Kucukmetin, A
Abstract : Introduction/Background: Minimal access approaches to radical hysterectomy for cervical cancer have become increasingly popular in the last decade and have been adopted broadly. Laparoscopic approach for cervical cancer trial (LACC) concluded more recurrence and higher mortality in minimal access group. These findings are supported by subsequent epidemiological data.To demonstrate that patients' care had not been compromised, we compared the outcomes of TARH (Abdominal radical hysterectomy) and TLRH (Laparoscopic radical hysterectomy) in our hospital in the past 10 years. Methodology: We performed a retrospective cohort study involving women who underwent radical hysterectomy for stage 1A2 - 2A cervical cancer during the January 2008 to December 2018 period at Northern Gynaecological Oncology Centre. All TARH was performed between 2008 to 2010. Overall and progression free survival were compared in the groups and compared with clinical variables using Cox proportional hazards regression and log rank test. Results: A total of 239 patients were included in our study.69 patients underwent TARH and 170 had TLRH. Both groups were comparable in baseline characteristics.1A2=1%, 1B1=81%, 1B2=15%, 2A=3%. With a median follow up time of 52 months there were no significant differences in mortality 13% vs 5% (hazard ratio 1.01; 95% confidence interval [CI], 0.36 to 2.82; P=0.98 by the log-rank test) or recurrence rate 15.9% and 7% (Hazard Ratio 1.46, 95% CI:0.59–3.59, p=0.41) in TARH and TLRH group respectively. Although mortality was not associated with route of surgery, it was associated with tumour size, and the presence of lymphovascular space invasion(p=0.007). Blood loss, transfusion requirements and post-operative complications were significantly lower in TLRH arm (p=0.03). Conclusion: Neither mortality nor recurrence was associated with route of surgery. There was a tendency of greater recurrence in the open radical hysterectomy arm, but this was not statistically significant. Disclosure: Nothing to disclose.